Hemolymph osmolality in mollusk Lymnaea stagnalis during acute experimental hyperglycemia - Sidorov, Alexander V. (Experimental Biology and Biotechnology, 2022)
It has been established that the development of hyperglycemia, accompanied by a multiple increase in the hemolymph glucose content (up to 4.0 – 4.5 mmol/L), doesn’t lead to any significant changes in Lymnaea’ s hemolymph osmolality. Incubation of mollusks in 100 mmol/L aqueous solution of polyethylene glycol 200 for 2 h causes a 1.4-fold increase in hemolymph osmolality (up to 210 mosmol/kg) compared to the control level.
Keywords: osmolality; glucose; invertebrates